Government Program Payment for Crop Cost-Return Budgets - Kastens, Terry L.; Lubben, Bradley D. (My University, 2002)
This publication provides estimated figures for producers to budget.
MF2236_2002_10
Keywords: MF2236; Economics; Crops; MF